Investigación en Efectividad y Mejora Escolar: ¿Nueva Agenda? - Carrasco Rozas, Alejandro (REICE. Revista Iberoamericana sobre Calidad, Eficacia y Cambio en Educación, 2016)
A partir de la reciente publicación del International Handbook of School Effectiveness and Improvement (Townsend, 2007), este comentario discute tanto sobre la dirección que esta tomando la investigación en efectividad y mejora escolar (IEM) en el mundo anglófono como la potencial contribución de una nueva agenda de mejora escolar a las políticas educativas destinadas a los sectores menos privilegiados de la población. Se incorpora un breve comentario sobre el desarrollo del paradigma de la efectividad en Latinoamericana. Descriptores: Política educativa, efectividad y mejora escolar, agenda contextualizada de mejora escolar. Research in School Effectiveness and School Improvement: ¿New Agenda? Drawing on the recent publication of the International Handbook of School Effectiveness and Improvement (Townsend, 2007), this review offers some insights about the current debates around the paradigm of school effectiveness and school improvement research. In particular, the review focuses on the increasing importance of a contextualized agenda of research and policy on school reform in the light of the ongoing concern about schools serving the most disadvantaged population. Likewise, the review includes some comments with respect to the development of this paradigm in Latin America. Keywords: Educational Policies, school effectiveness, school improvement, contextualized agenda.